2019
DOI: 10.1001/jamapsychiatry.2018.3637
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Brain Metabolism With 7-T Proton Magnetic Resonance Spectroscopy in Patients With First-Episode Psychosis

Abstract: IMPORTANCEThe use of high-field magnetic resonance spectroscopy (MRS) in multiple brain regions of a large population of human participants facilitates in vivo study of localized or diffusely altered brain metabolites in patients with first-episode psychosis (FEP) compared to healthy participants. OBJECTIVE To compare metabolite levels in 5 brain regions between patients with FEP (evaluated within 2 years of onset) and healthy controls, and to explore possible associations between targeted metabolite levels an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
149
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 149 publications
(172 citation statements)
references
References 79 publications
22
149
0
1
Order By: Relevance
“…This is not surprising, given that meta-analytic pooling of ACC GSH studies in schizophrenia reveal a small overall effect size [24], suggesting the possibility of heterogeneity in the GSH levels and thus redox status among patients. Our results suggest that such heterogeneity may map onto antipsychotic responsiveness, resulting in the conflicting findings of GSH levels reported to date in schizophrenia [23].…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…This is not surprising, given that meta-analytic pooling of ACC GSH studies in schizophrenia reveal a small overall effect size [24], suggesting the possibility of heterogeneity in the GSH levels and thus redox status among patients. Our results suggest that such heterogeneity may map onto antipsychotic responsiveness, resulting in the conflicting findings of GSH levels reported to date in schizophrenia [23].…”
Section: Discussionmentioning
confidence: 65%
“…A previous 7T MRS study included FEP subjects with an average of 55 weeks of antipsychotic exposure [54], compared with 6 days of median exposure in our sample. A more recent study [23] included FEP subjects with up to 2 years of illness duration, while we recruited all subjects during the acute first episode (mean SOFAS score of 38.1). We report three major findings: (1) patients with FEP with higher GSH levels in ACC show a rapid symptom reduction upon starting antipsychotic treatment, (2) when compared with healthy controls, GSH levels in patients are dissociated from glutamate levels, and (3) Glutamate excess predicts the degree of Social and Occupational dysfunction seen at the time of presentation with FEP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher field strength has greater sensitivity, enabling greater separation of glutamate and glutamine peaks, and allowing for more accurate quantification. Two studies in first‐episode patients have shown reduced glutamate concentrations in the anterior cingulate cortex, while another only found this in a subset of patients with predominantly negative symptoms. No difference has been observed in several other investigations.…”
Section: Glutamatementioning
confidence: 91%
“…Most psychiatric and neurodegenerative illnesses are characterized by cognitive impairments (Claesdotter, et al, 2018;Jagust, 2018;Wang, et al, 2019;Wunderli, et al, 2016).…”
Section: Introductionmentioning
confidence: 99%